Flux pinning landscape up to 25 T in SmBa2Cu3Oy films with BaHfO3 nanorods fabricated by low-temperature growth technique. (4th September 2017) - Tsuchiya, Yuji; Miura, Shun; Awaji, Satoshi; Ichino, Yusuke; Matsumoto, Kaname; Izumi, Teruo; Watanabe, Kazuo; Yoshida, Yutaka
Abstract: RE Ba2 Cu3 O y superconducting tapes are appropriate for high field magnet applications at low temperatures (i.e. below liquid nitrogen temperature). To clarify the morphology and the volume of the effective pinning center at low temperatures, we used a low-temperature growth technique to fabricate SmBa2 Cu3 O y (SmBCO) films with various amounts of BaHfO3 (BHO) nanorods onto MgO-buffered metal substrates produced by ion-beam-assisted deposition; we investigated their flux pinning properties using a 25 T cryogen-free superconducting magnet that was recently developed at Tohoku University. According to the microstructural analysis using transmission electron microscopy, the BHO nanorods have a content-dependent morphology and are aligned for the higher content. The inclined and discontinuous BHO nanorods were observed in SmBCO films with BHO contents up to 3.8 vol%; they show an excellent flux pinning force density (1.5 TN m −3 at 21 T and 4.2 K) even when the magnetic field is perpendicular to the films. Based on the effective mass model for the flux pinning, the random pinning centers are dominant at low temperatures. The correlated flux pinning is stronger for aligned nanorods; however, the random pinning center becomes weaker in the 4.5 vol% BHO-doped films. Therefore, the optimal BHO doping level is approximately 3.8 vol% in terms of the amplitude of the critical current density and the anisotropy from 4.2 K to 20 K because this provides the best mixture of correlated and random flux pinning centers.